Feeling the Body: Performance, Torture and Masochism in Spanish Conceptualisms - Albarran Diego, Juan (Arte, Individuo y Sociedad, 2013)
This paper analyzes the relationship between the violence exercised by the Franco governement over the dissident bodies —on anyone who would present a threat to the maintenance of the dictatorship—, and some performative strategies close to the practices included under the label “nuevos comportamientos”. These conceptual works were related with a kind of masochism, with a desire to promote tactile aspects —through self-inflicted pain— and with a phenomenological exploration of reality. Following the studies of Kathy O’Dell and Sophie Delpeux, this text aims to provide new political readings of several performances by highlighting the role of the photographic medium in their reception and contextualizing these works in the very complex political Spanish transition.